2010
DOI: 10.1177/00333549101250s508
|View full text |Cite
|
Sign up to set email alerts
|

10 Guiding Principles of a Comprehensive Internet-Based Public Health Preparedness Training and Education Program

Abstract: Distance learning is an effective strategy to address the many barriers to continuing education faced by the public health workforce. With the proliferation of online learning programs focused on public health, there is a need to develop and adopt a common set of principles and practices for distance learning. In this article, we discuss the 10 principles that guide the development, design, and delivery of the various training modules and courses offered by the North Carolina Center for Public Health Preparedn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Training modalities are not one-size-fits-all. Formative research with groups before development and implementation should be used to determine what is needed by the training's target audience ( 30 , 34 ). Unique individuals make up the public health workforce, and we should be cognizant of the diverse needs of those individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Training modalities are not one-size-fits-all. Formative research with groups before development and implementation should be used to determine what is needed by the training's target audience ( 30 , 34 ). Unique individuals make up the public health workforce, and we should be cognizant of the diverse needs of those individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Scaling up capacity building approaches is a significant issue in implementation science ( 33 ). Much of the literature on public health workforce training in distance or blended learning (combination of in-person and distance) formats focuses on single topics or specific skills ( 31 , 32 , 34 43 ), with few focusing on the utility of training modes for scale-up potential ( 44 , 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…Budgets and policy statements should reflect commitment to the program. Seven authors agreed on the positive effect of planning, describing objectives and expectations, and placing these in a timeline to maximize efficiency [ 7 , 23 , 36 , 37 , 39 , 40 , 49 ]. Cook et al [ 50 ] identified potential barriers to implementation, and Olson et al [ 20 ] advised readers to develop a marketing plan for reaching end users.…”
Section: Resultsmentioning
confidence: 99%
“…Navigation should be user friendly and intuitive with a “less is more” design strategy. The design should be visually pleasing, adhere to the principles of excellent website design, and use reusable learning objects for a standard look and feel [ 37 , 45 ]. Four articles provided a minimal set of pages/functionalities: glossary of terms, frequently asked questions, concept map, references cited, abbreviation key, and labelled diagrams [ 36 , 45 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…6 Workforce development training has been characterized by levels of cognitive learning whereby participant knowledge, skill, and ability to perform specific tasks increase as the level of instruction and opportunities to practice skills increase. 7,8 Basic learning approaches are designed to increase content knowledge, awareness, and understanding. Midlevel approaches provide opportunities to apply concepts and skills in the content area.…”
mentioning
confidence: 99%